Analisis Potensi Equator Park Dalam Meningkatkan Kesejahteraan Masyarakat Di Desa Jeruju Besar - Yohanes, Yulias; Amboisa, Nadia Fransiska; Pratiwi, Angelika Yuni; Aprianti, Syapri; Oksa, Oksa (PT. Riset Press International, 2024)
Equator Park Jeruju Besar is a new educational tourist attraction located in Kubu Raya Regency, West Kalimantan. This location is located in Karya Bhakti Hamlet, Jeruju Besar Village, Sungai Kakap District, which has great potential in introducing the outside world to tourism, especially about mangrove and mangrove tourism. This area has been established for two years and is still being developed for mangrove and mangrove tourism. The development potential of this place is very large because of its strategic location and not far from the city center. Apart from improving tourism facilities in the Kubu Raya area, improving and improving the quality of existing tourist destinations is also important because this will have an impact on improving the standard of living of the local community. Ecotourism is an environmentally friendly tourism concept that can minimize adverse impacts on the natural, social, cultural and livelihoods of local communities. The concepts of village tourism and ecotourism have similarities in terms of preservation, consolidation and community involvement for the sake of long-term tourism expansion. The Equator Park area in Jeruju Besar Village improves the economic, social and cultural conditions around this tourist community area. The development of the Equator Park area in Jeruju Besar Village was developed with community participation, as an effort to empower and increase human potential, especially young people. The plan to expand the Jeruju Equatorial Park area is in collaboration with Karang Taruna to build paths, gazebos and gates in the Jeruju Equatorial Park area. This area has superior potential for development, such as culinary tourism, historical tourism and accommodation. Tourism potential in Jeruju Besar Village must be developed in a way that is environmentally, socially, culturally and friendly to the lives of local communities. The development of the Equator Park area in Jeruju Besar Village will be one of the choices for tourists visiting Kubu Raya Regency. This research aims to analyze the regional potential of Equator Park Tourism in Jeruju Besar Village, Sungai Kakap District, Kubu Raya Regency, West Kalimantan Province. The method used in this research is a qualitative approach involving field surveys, in-depth interviews, observations and document analysis. Focusing on aspects such as tourist attraction, infrastructure, accessibility and local economic potential, this research groups the factors that influence the development and marketing of these tourist destinations. The results of the analysis provide insight into the potential and challenges faced by Equator Park Jeruju Besar as well as recommendations for increasing the use of tourism potential to support local economic development.